Converting Web Site Visitors into Buyers: How Web Site Investment Increases Consumer Trusting Beliefs and Online Purchase Intentions - Schlosser, Ann E.; White, Tiffany Barnett; Lloyd, Susan M. (Journal of Marketing, 2006)
The authors investigate the impact of Web site design investments on consumers’ trusting beliefs and online purchase intentions. Such investments signal the component of trusting beliefs that is most strongly related to online purchase intentions: ability. These effects were strongest when consumers’ goals were to search rather than to browse and when purchases involved risk.